Tracking MET de-addiction in lung cancer: A road towards the oncogenic target. (November 2017) - Pilotto, S.; Carbognin, L.; Karachaliou, N.; Ma, P.C.; Rosell, R.; Tortora, G.; Bria, E.
Highlights: The identification of new effective targets in lung cancer remains a high priority. No impactful results have been achieved with anti-MET agents in unselected NSCLC patients. MET exon 14 skipping mutations recently emerged as a novel actionable oncogenic target. MET exon 14 mutant patients should be enrolled in clinical trials with anti-MET agents. Emerging mechanisms of resistance to MET inhibition support the combinatorial strategy. Abstract: The discovery of druggable oncogenic drivers (i.e. EGFR and ALK ), along with the introduction of comprehensive tumor genotyping techniques into the daily clinical practice define non-small-cell lung cancer (NSCLC) as a group of heterogeneous diseases, requiring a context-personalized clinico-therapeutical approach. Among the most investigated biomarkers, the MET proto-oncogene has been extensively demonstrated to play a crucial role throughout the lung oncogenesis, unbalancing the proliferation/apoptosis signaling and influencing the epithelial-mesenchymal transition and the invasive phenotype. Nevertheless, although different mechanisms eliciting the aberrant MET-associated oncogenic stimulus have been detected in lung cancer (such as gene amplification, increased gene copy number, mutations and MET/HGF overexpression), to date no clinically impactful results have been achieved with anti-MET tyrosine kinase inhibitors and monoclonal antibodies in the context of an unselected or MET enriched population. Recently, MET exon 14 splicing abnormalities have been identified as a potential oncogenic target in lung cancer, able to drive the activity of MET inhibitors in molecularly selected patients. In this paper, the major advancement and drawbacks of MET history in lung cancer are reviewed, underlying the renewed scientific euphoria related to the recent identification of MET exon 14 splicing variants as an actionable oncogenic target.